Template-Based Efficient Resource Provisioning and Utilization in Cloud Data-Center - Chowhan, Seema; Kumar, Ajay; Shirwaikar, Shailiaja (International Journal of Computer Sciences and Engineering, 2019)
Cloud computing, with an ever-growing interest, with the promise of revolving computing as a utility after water, electricity, gas and telephony is currently at a stage, where many enterprises are considering adapting to this technology. Resource provisioning policies allow efficient sharing of resources available in a data center and these policies help to evaluate and enhance the cloud performance. Resource provisioning that maintains quality of service with optimum resource utilization is a challenge. It is a multidimensional problem that can have issue based solution in the form of a set of services that help allocation and negotiation of service level agreements. A cloud simulator environment is used and experiments are performed by varying different parameters of Virtual Machines (VM) and the tasks running on VM, to get optimal values for designing templates. The proposed template based resource provisioning (TBRP) method overcomes under-provisioning and over-provisioning of resources for agreed parameters specified by SLA.